Breve reseña histórica de la evolución y el desarrollo del derecho a la educación - Torres Victoria, Nancy (Revista Electrónica Educare, 2008)
This article seeks to illustrate the path that the conception of the Right to Education has followed and the interpretation that has being made of it in the different stages. In each one of these stages, the experts in the subject have categorized this Right from the beginning, locating it among Human Rights in the fundamental place that it deserves, or that should deserve, serving as an entrance door to the enjoyment of a full social citizenship, that becomes aware and guarantor of many other Rights that derive from it.